Sosialisasi Sistem Peradilan Pidana dan Lembaga Bantuan Hukum Dalam Rangka Meningkatkan Pemahaman Masyarakat Tentang Akses Keadilan dan Perlindungan Hukum - Zulwisman Zulwisman; Raymond George Ias Silalahi; Nurhalizah Nurhalizah; Natalia Putri Silaban; Lauren Aprilia Putri Nainggolan; Marwah Vassha Genia; Kanaya Sava Nabira; Rohit Trianddy; Hamizan Miftah; Sampit Rezeki Manik; Aulia Khairuna Hasibuan (Unri Conference Series: Community Engagement, 2025)
The low level of public understanding of the criminal justice system in Indonesia remains a fundamental issue that limits access to justice. This condition is most evident in rural areas, where legal literacy among the community is still low and the utilization of Legal Aid Institutions (LBH) has not been optimal. Through the 2025 MBKM Community Service Program (KUKERTA) of Universitas Riau, a legal education initiative was conducted in Bukit Melintang Village to enhance public understanding of the criminal justice system and the role of LBH in providing legal assistance. The activity employed a participatory approach through lectures, interactive discussions, case simulations, and the creation of legal educational media. Based on a survey involving 40 participants, the community’s understanding of the criminal justice system increased from 25% before the activity (pre-test) to 85% after the activity (post-test). Knowledge regarding the role of LBH rose from 30% to 90%, and the willingness of the community to access legal services increased from 40% to 75%. These improvements were measured through pre-test and post-test surveys as well as evaluative interviews with participants and village officials. Community enthusiasm was reflected in their active participation during discussions and their encouragement for the program to be continued. The activity also resulted in a recommendation to establish a Village Legal Consultation Post in Bukit Melintang as a sustainable follow-up effort. Therefore, this program not only strengthens the community’s legal literacy but also contributes significantly to realizing Bukit Melintang Village as a Law-Aware Village (Desa Sadar Hukum).